Incentive Structures, Labour Performance, and Fruit Quality: Panel Evidence from a South African Deciduous Fruit Operation (2017–2019) - Segole, Kagiso (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.